Hollywood's Absent, Impotent, and Avenging God in the Classroom - O'Keeffe, Michael E. (Horizons, 2003)
The focus of this article is twofold. First, recognizing the influence of the mass media on the religious views of many undergraduate students, it examines the negative depiction of God in several popular American films and concludes that the image of God as absent, impotent and demonic ought to be addressed in the classroom. The second issue concerns the use of film in the classroom—both to encourage students to sharpen their understanding of contemporary theology, and to then use this theology as a basis for understanding and evaluating the religious messages carried by contemporary films. The films explored are What Dreams May Come, Dogma, The End of the Affair, The Rapture, and Stigmata.